THE INFLUENCE OF PRODUCT QUALITY, PRICE, AND PRODUCT DESIGN ON CONSUMER PURCHASING DECISIONS OF EIGER PRODUCTS - Krido Eko Cahyono (INTERNATIONAL, Journal of Sharia Business Management, 2026)
This research aimed to determine the effect of product quality, price and product design on the purchasing decisions of Eiger products in 2022. The independent variables were product quality, price and product design, whilst the dependent variable was purchasing decisions. The research was quantitative. Furthermore, the data collection technique employed purposive sampling, wherein the sample was selected based on specified criteria. Additionally, the data collection instrument utilised questionnaires. The questionnaires were distributed to 100 respondents as the sample. Additionally, the data analysis technique employed multiple linear regression using SPSS (Statistical Product and Service Solutions) 25. The results concluded that product quality had a significant effect on purchasing decisions regarding Eiger products. Similarly, price had a significant effect on purchasing decisions regarding Eiger products. Likewise, product design had a significant effect on purchasing decisions regarding Eiger products..